1998
DOI: 10.1520/jfs14347j
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Criminal Activity Between Heroin Abusers and Subjects Without Psychiatric Disorders—Analysis of 578 Detainees in Bilbao, Spain

Abstract: The association between drug abuse and criminal activity has been deeply established, but the nature of this relationship is controversial. The incidence and types of criminal activity were analyzed in 837 arrests of 578 subjects who were also interviewed for psychiatric diagnosis and evaluation of criminal responsibility. There was a significant prevalence of heroin abuse/dependence (50.5 %) in the sample. Another 124 subjects (21.5 %) in whom no psychiatric disorder could be observed were considered as the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 22 publications
2
6
0
1
Order By: Relevance
“…In the current study, greater substance use risk was representative of a minimum of one severe substance use disorder, injection drug use, and drug use within the week prior to jail admission. These three factors are consistent with frequent and heavy drug use, which prior research has clearly shown to correspond to heightened involvement in acquisitive crimes, serving primarily as income-generating activities (Cross et al, 2001; Hayhurst et al, 2017; Morentin, Callado, & Meana, 1998; Skjӕrvø, Skurtveit, Clausen, & Bukten, 2017; van der Zanden, Dijkgraaf, Blanken, van Ree, & van den Brink, 2007). Injection drug use garners special attention, primarily because this practice typically involves the administration of heroin, or a combination of several drugs, but also because users who report injecting drugs have explicitly indicated they would forego illegal income generation if they were not acting to purchase drugs (DeBeck et al, 2007).…”
Section: Discussionsupporting
confidence: 74%
“…In the current study, greater substance use risk was representative of a minimum of one severe substance use disorder, injection drug use, and drug use within the week prior to jail admission. These three factors are consistent with frequent and heavy drug use, which prior research has clearly shown to correspond to heightened involvement in acquisitive crimes, serving primarily as income-generating activities (Cross et al, 2001; Hayhurst et al, 2017; Morentin, Callado, & Meana, 1998; Skjӕrvø, Skurtveit, Clausen, & Bukten, 2017; van der Zanden, Dijkgraaf, Blanken, van Ree, & van den Brink, 2007). Injection drug use garners special attention, primarily because this practice typically involves the administration of heroin, or a combination of several drugs, but also because users who report injecting drugs have explicitly indicated they would forego illegal income generation if they were not acting to purchase drugs (DeBeck et al, 2007).…”
Section: Discussionsupporting
confidence: 74%
“…However, the authors also suggest that the level of aggressiveness demonstrated by the methadone patients seemed to be related more to personality traits than to drug effects. Moreover, a recent study conducted in Spain (Morentin, Callado, & Meana, 1998), which consisted of a review of the files of 578 recently arrested individuals, concluded that among those arrestees who were heroin abusers, aggression or resistance to police authorities and nonfatal violent offenses against persons were less frequent (3.7% and 3%, respectively) than among those arrestees for whom there was no drug or psychiatric diagnosis (12% and 13.7%, respectively). Obviously there is some inconsistency in the literature.…”
Section: Opiates (Morphine Heroin and Codeine)mentioning
confidence: 99%
“…Heroin use is also associated with a number of adverse social consequences. World-wide, the illicit use of opiates is considered to be a contributory factor in property crime and crimes of violence [8], with the US Arrestee Drug Abuse Monitoring (ADAM) Project reporting that more than 10% of male arrestees in eight of the 27 ADAM sites tested positive for recent opiate use in 2000 [9].…”
Section: Introductionmentioning
confidence: 99%